Invariant chain protects class II histocompatibility antigens from binding intact polypeptides in the endoplasmic reticulum. - Busch, Robert; Cloutier, Isabelle; Sékaly, Rafick-Pierre; Hämmerling, Günter J. (The EMBO journal, 1996)
Unlike class I histocompatibility (MHC) antigens, most newly synthesized MHC class II molecules fail to be loaded with peptides in the endoplasmic reticulum (ER), binding instead to the invariant chain glycoprotein (Ii). Ii blocks the class II peptide binding groove until the class II:Ii complexes are transported to endosomes where Ii is removed by proteolysis, thus permitting loading with endosomal short peptides (approximately 12-25 amino acids). Ligands from which the groove is protected by Ii have not yet been identified; theoretically they could be short peptides or longer polypeptides (or both), because the class II groove is open at both ends. Here we show that in Ii‐ deficient cells, but not in cells expressing large amounts of Ii, a substantial fraction of class II alpha beta dimers forms specific, SDS‐resistant 1:1 complexes with a variety of polypeptides. Different sets of polypeptides bound to H‐2Ak, Ek, Ed and HLA‐DR1 class II molecules; for Ak, a major species of Mr 50 kDa (p50) and further distinct 20 and 130 kDa polypeptides were detectable. Class II binding of p50 was characterized in detail. Point mutations within the Ak antigen binding groove destabilized the p50:class II complexes; a mutation outside the groove had no effect. A short segment of p50 was sufficient for association with Ak. The p50 polypeptide was synthesized endogenously, bound to Ak in a pre‐Golgi compartment, and was transported to the cell surface in association with Ak. Thus, Ii protects the class II groove from binding endogenous, possibly misfolded polypeptides in the ER. The possibility is discussed that polypeptide binding is an ancestral function of the MHC antigen binding domain.